The complete mitochondrial genome of the Basidiomycete edible fungus Pleurotus eryngii. Issue 1 (1st January 2016) - Yang, Ruiheng; Li, Yan; Li, Chuanhua; Xu, Jianping; Bao, Daopeng
Abstract: The complete mitochondrial genome of the edible fungus Pleurotus eryngii (oyster mushroom) was determined using Illumina sequencing. This mitogenome is a circular molecule of 72, 650 bp in length with a GC content of 26.28%. Gene prediction showed that 40 putative protein-coding genes, the small ribosomal RNA subunits (rns), and 23 tRNAs were located on the same strand. The mitogenome of P. eryngii has a similar structure to that of P. ostreatus in both gene content and gene order. The mitogenome information of P. eryngii should contribute to our understanding of the diversity and evolution of Pleurotaceae and Agaricales.